To Find Out the Role of C-Reactive Protein in Acute Myocardial Infarction as a Marker of Prognosis (Medical Forum Monthly, 2023)
Objective: To find out the role of CRP in acute MI as a marker of prognosis.Study Design: Cross sectional studyPlace and Duration of Study: This study was conducted at the Medicine & Cardiology at Khyber Teaching Hospital Peshawar. Duration: March 2021 to February 2022.Materials and Methods: Selection of subjects was done according to the inclusion and exclusion criteria followed by diving them into two cohorts; Acute MI patients that developed complications (Group I N=30) and a second group that didn’t develop complications post MI during the hospital stay (Group II N=34). Blood for CRP Levels was taken and analysed at the Hospital Lab. The data was analysed using SPSS version 26.0 for MacBook Pro and organised as tables.Results: CRP levels showed statistical significance (p<0.05) for both groups, with higher values for group I (5.14 mg/L ± 2.16mg/L) in comparison with group II (1.09 mg/L ± 0.96mg/L) subjects.Conclusion: Our study found a direct relation between CRP levels and post MI complications and hence is a good prognostic marker in acute MI. The higher levels of CRP in group I show that raised CRP levels post MI are associated with the complications during hospital stay.